2008
DOI: 10.2208/proce1989.55.1396
|View full text |Cite
|
Sign up to set email alerts
|

Field Survey of Storm Surge Disaster due to Cyclone Sidr in Bangladesh

Abstract: Field surveys were performed in the southwest of Bangladesh to learn lessons out of severe disasters due to Cyclone Sidr. Spatial distributions of inundation heights were measured around the most damaged area. Inundation heights along the Baleshwar river and the Burishwar river were relatively high compared to those observed on the coast of Kuakata although these sites are far from the coast. Detailed surveys were thus performed in these three areas and there found several residents who witnessed bore-like wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The details of the storm surge computation model being employed in the present paper and its validity for the present study area can be found in Hussain and Tajima [10], Tajima et al [8] and Shibayama et al [28]. Among these, Tajima et al [8] and Shibayama et al [28] applied inundation data collected after Cyclone Sidr of 2007 to validate the numerical model.…”
Section: The Numerical Model and Its Applicabilitymentioning
confidence: 99%
“…The details of the storm surge computation model being employed in the present paper and its validity for the present study area can be found in Hussain and Tajima [10], Tajima et al [8] and Shibayama et al [28]. Among these, Tajima et al [8] and Shibayama et al [28] applied inundation data collected after Cyclone Sidr of 2007 to validate the numerical model.…”
Section: The Numerical Model and Its Applicabilitymentioning
confidence: 99%
“…Distances are from the river shore and inundation height from the river water level (numbers in parenthesis is from the ground level). (Shibayama et al, 2009a) Figure 1. Survey route and measured storm surge height.…”
Section: A Case Of Cyclone Sidr In Bangladeshmentioning
confidence: 99%
“…Survey route and measured storm surge height. (Shibayama et al, 2009a) years ago but they were broken due to erosion before Sidr attacked them. Though newer banks had been built recently about 150 m inside from these older banks, the high tide due to Sidr flowed over their tops of about 2.5 m over the river water at the measurement time.…”
Section: A Case Of Cyclone Sidr In Bangladeshmentioning
confidence: 99%
See 2 more Smart Citations